1977
DOI: 10.1098/rspb.1977.0040
|View full text |Cite
|
Sign up to set email alerts
|

1 H nuclear magnetic resonance studies of Lactobacillus casei dihydrofolate reductase: effects of substrate and inhibitor binding on the histidine residues

Abstract: The effects of the binding of substrates and inhibitors (folate, dihydro­folate, folinic acid, trimethoprim, methotrexate and aminopterin) to Lactobacillus casei dihydrofolate reductase on the histidine residues of the enzyme have been studied by 1 H n. m. r. spectroscopy. The more weakly binding (rapidly exchanging) inhibitors 2, 4-diaminopyrimidine and p -aminobenzoyl-l-glutamate, which can be regarded as ‘fragments’ of methotrexate, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The decrease in pK of His 18 accompanying methotrexate binding (Table 3) appears to reflect an inhibitor-induced conformational change (Birdsall et al, 1977;Wyeth et al, 1980;Gronenbom et al, 1981); this decrease in pK appears to be essentially the same for the a-and y-amides as for methotrexate itself. However, significantly larger decreases are observed for both the a,y-diamide and the a,y-dimethyl ester, indicating a significantly different mode of binding.…”
Section: Effects Of Inhibitor Binding On Histidine Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in pK of His 18 accompanying methotrexate binding (Table 3) appears to reflect an inhibitor-induced conformational change (Birdsall et al, 1977;Wyeth et al, 1980;Gronenbom et al, 1981); this decrease in pK appears to be essentially the same for the a-and y-amides as for methotrexate itself. However, significantly larger decreases are observed for both the a,y-diamide and the a,y-dimethyl ester, indicating a significantly different mode of binding.…”
Section: Effects Of Inhibitor Binding On Histidine Residuesmentioning
confidence: 99%
“…(Birdsall et al, 1977;Wyeth et al, 1980;Gronenborn et al, 1981), and assignments for all their C2-proton resonances are now available (Wyeth et al, 1980; Birdsall, J. Feeney and G.C.K. Roberts, unpublished work), although some of these remain tentative.…”
Section: Effects Of Inhibitor Binding On Histidine Residuesmentioning
confidence: 99%
“…Fluorometric measurements of the binding of 2,4-diaminopyrimidine and p-aminobenzoyl-L-glutamate to Lactobacillus casei cells revealed that the two fragments bind the bacterial enzyme simultaneously and cooperatively (5,6). Moreover, a recent study concerning the in vitro evaluation of the antimalarial activity of pyrimethamine and sulfadoxine against Plasmodium falciparum also suggested the simultaneous-inhibition hypothesis as a possible mechanism of potentiation (13).…”
mentioning
confidence: 99%
“…Dihydrofolate reductase (5,6,7,8-tetrahydrofolate: NADP+ oxidoreductase; EC 1.5.1.3), which catalyzes the NADPH-dependent reduction of dihydrofolate to tetrahydrofolate, has been regarded as one of the crucial targets for bacterial and protozoal chemotherapy. The enzyme was shown to be the molecular site of action of a number of antifolates (2,8,32).…”
mentioning
confidence: 99%
“…1 pK unit higher than its value in the ligand-free enzyme ( Figure 17) [130,131] This value reflects the interaction of His 28 with the MTX g-carboxylate group ( Figure 13) and provides an excellent method for monitoring interactions involving His 28. [132] We have used these effects to study complexes of L. casei DHFR with the a-and g-amide (5); (!)…”
Section: Interactions Of His 28 With Carboxylate Groupsmentioning
confidence: 98%